Study on the effective dose of alfentanil combined with ciprofol in inhibiting intraoperative body movement responses in patients undergoing breast lump resection - Li, Fei; Lu, Yingying; Lu, Gang; Gu, Jiaqi; Zhu, Yumin (Frontiers in Medicine, 2026)
BackgroundAlfentanil and ciprofol are used in combination for intravenous anesthesia, but the effective dose of alfentanil required to suppress movement during surgery when co-administered with ciprofol is not well-defined. This study aimed to determine the effective dose of alfentanil, combined with ciprofol, required to inhibit body movement responses in patients undergoing breast lumpectomy.MethodsPatients scheduled for elective breast lumpectomy uswere selected. Ciprofol was administered intravenously at anesthesia induction, and alfentanil was given using the sequential method with an initial dose of 10 μg/kg and a dose gradient of 1 μg/kg. The dosage of alfentanil, the incidence of intraoperative respiratory depression, hypotension requiring treatment, and bradycardia were recorded. Postoperative adverse reactions were assessed and recorded. Probit regression analysis was used to calculate the effective dose.ResultsThe median effective dose (ED₅₀) of alfentanil for inhibiting intraoperative body movement was calculated to be 13.396 μg/kg, with a corresponding 95% effective dose (ED95) of 15.752 μg/kg. During the surgical procedure, no patients required therapeutic intervention for either intraoperative hypotension or bradycardia. However, three patients developed respiratory depression. Notably, no postoperative adverse reactions were documented in any of the study participants.ConclusionThe ED50 of alfentanil combined with ciprofol for intravenous anesthesia to suppress movement during breast lumpectomy is 13.396 μg/kg, and the ED₉₅ is 15.752 μg/kg.Clinical trial registrationhttp://www.chictr.org.cn, ChiCTR2500109829.